A structural view of synthetic cofactor integration into [FeFe]-hydrogenases. Issue 2 (9th November 2015) - Esselborn, J.; Muraki, N.; Klein, K.; Engelbrecht, V.; Metzler-Nolte, N.; Apfel, U.-P.; Hofmann, E.; Kurisu, G.; Happe, T.
Abstract : Crystal structures of semisynthetic [FeFe]-hydrogenases with variations in the [2Fe] cluster show little structural differences despite strong effects on activity. Abstract : [FeFe]-hydrogenases are nature's fastest catalysts for the evolution or oxidation of hydrogen. Numerous synthetic model complexes for the [2Fe] subcluster (2FeH ) of their active site are known, but so far none of these could compete with the enzymes. The complex Fe2 [μ-(SCH2 )2 X](CN)2 (CO)4 2− with X = NH was shown to integrate into the apo-form of [FeFe]-hydrogenases to yield a fully active enzyme. Here we report the first crystal structures of the apo-form of the bacterial [FeFe]-hydrogenase CpI from Clostridium pasteurianum at 1.60 Å and the active semisynthetic enzyme, CpI ADT, at 1.63 Å. The structures illustrate the significant changes in ligand coordination upon integration and activation of the [2Fe] complex. These changes are induced by a rigid 2FeH cavity as revealed by the structure of apoCpI, which is remarkably similar to CpI ADT . Additionally we present the high resolution crystal structures of the semisynthetic bacterial [FeFe]-hydrogenases CpI PDT (X = CH2 ), CpI ODT (X = O) and CpI SDT (X = S) with changes in the headgroup of the dithiolate bridge in the 2FeH cofactor. The structures of these inactive enzymes demonstrate that the 2FeH -subcluster and its protein environment remain largely unchanged when compared to the active enzyme CpI ADT . As the active site shows an open coordination site in all structures, the absence of catalytic activity is probably not caused by steric obstruction. This demonstrates that the chemical properties of the dithiolate bridge are essential for enzyme activity.